The Influence of “Renewable Energy Directive II” Policy for The Sustainability of Palm Oil Industry in Indonesia - Cindy Fabrizia Suling; Eko Priyo Purnomo; Klaus Hubacek; Prathivadi Anand (Universitas Sultan Ageng Tirtayasa, 2023)
The purpose of this study is to see how the European Union's RED II policy affects the palm oil industry in Indonesia. One of the things the European Union is doing to achieve its sustainability goals is developing and enforcing a directive called the European Union Renewable Energy Directive (EU RED). The Renewable Energy Directive (RED) is a set of regulations that aim to increase the use of renewable energy sources within the European Union. The emergence of the RED policy had an impact on the Indonesian palm oil industry because it was assessed that the use of oil palm land in Indonesia had a significant impact on deforestation. The existence of this policy has caused the Indonesian government to bring up various kinds of regulations from year to year that regulate the palm oil industry. This research is qualitative and uses secondary data types; the data used comes from various kinds of national news and journals as well as document reports from the government.